A pharmaceutical study on modified dosage forms of a certain anti migraine drug - Manal Medhat Ahmed Ali Eneibar; Aly Ahmed Abdelbary; Mohamed Ahmed Elnabarawi; Samia Hassan Shalaby (Cairo : Manal Medhat Ahmed Ali Eneibar, 2016)
Migraine is a common, chronic disorder. Clinically, migraine is characterized by recurrent attacks of headache followed by neurological and visual disturbances. Migraine greatly affects quality of life. WHO ranks migraine among the world{u2019}s most disabling medical illness. Sublingual administration is intended where the dosage form is placed under the tongue aiming for the drug to reach directly into the blood stream through the ventral surface of the tongue and floor of the mouth. The sublingual route usually produces a faster onset of action than orally ingested drug and the portion absorbed through the sublingual vessels bypasses the hepatic first pass metabolism and thus produces acceptable bioavailability. The absorption of the drug through the sublingual route is 3 to 10 times greater than the oral route. Sublingual dosage forms can be divided into sublingual tablets, sublingual films and sublingual sprays. Sublingual tablets are usually small tablets that must dissolve or disintegrate quickly in small volume of saliva to allow the drug to be absorbed quickly. They can be divided into fast disintegrating sublingual tablets and bioadhesive sublingual tablets
Thesis (Ph.D.) - Cairo University - Faculty of Pharmacy - Department of Pharmaceutics
Issued also as CD
Keywords: Anti migraine drug; Headache; Modified dosage forms